2004
DOI: 10.1108/10610420410568426
|View full text |Cite
|
Sign up to set email alerts
|

Building brand loyalty through individual stock ownership

Abstract: Building brand loyalty has become more important, yet more difficult to achieve in today's marketplace. This research investigates a possible avenue for building brand loyalty that is not directly related to the marketing of the product -attracting individual investors in the brand's corporate parent. A survey of over 500 individual investors revealed that individual investors do tend to buy brands from companies in which they hold stock, and investors may buy stock in a company because they have experience wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 17 publications
2
49
0
2
Order By: Relevance
“…Nevertheless, both marketing (Schoenbachler, Gordon, and Aurand, 2004;Vogelheim, Schoenbachler, and Gordon, 2001) and finance researchers (Frieder and Subrahmanyam, 2005) have recently begun to point out and find evidence of the fact that individuals who engage in buying and using the products and services of certain companies may also engage in investing in and holding the same companies' shares. In this light, it seems that managers have paid too little attention to and underestimated the significance of the segments of people who may act both as customers and shareholders to their companies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, both marketing (Schoenbachler, Gordon, and Aurand, 2004;Vogelheim, Schoenbachler, and Gordon, 2001) and finance researchers (Frieder and Subrahmanyam, 2005) have recently begun to point out and find evidence of the fact that individuals who engage in buying and using the products and services of certain companies may also engage in investing in and holding the same companies' shares. In this light, it seems that managers have paid too little attention to and underestimated the significance of the segments of people who may act both as customers and shareholders to their companies.…”
Section: Introductionmentioning
confidence: 99%
“…4 products and services. For instance, Schoenbachler et al (2004) recently investigated whether individuals' share ownership in companies increased their brand loyalty towards and repeat purchases of the products of those companies. Their findings suggested that individuals do tend to buy products from companies in which they hold shares.…”
Section: Introductionmentioning
confidence: 99%
“…According to [22] supported the above argument pointing out that a brand with a good image has the ability to reduce the product perception risk of the consumers and increase positive response from consumers. The qualities of product are an attribute of an established brand name and stimulate buying intention [3].…”
Section: Conceptual Frameworkmentioning
confidence: 66%
“…The repeat purchase (behavioral loyalty) may not reflect the true loyalty as it might buy through bribes such as price discount and coupons (Dick and Basu, 1994; Light, 1997 as cited in Schoenbachler et al, 2004). Thus, it is not a sufficient concept of brand loyalty as there is difference between brand loyalty and repeat buying behavior.…”
Section: Brand Loyalty -Attitudinal and Behavioral Loyaltymentioning
confidence: 99%
“…This had been supported by Ha, Janda, and Park (2008) which found that there is strong correlation exists between loyalty and the mean number of different stores visit per week. Moreover, the loyal consumers are likely to be less price sensitive, pass on the positive recommendation about the brand and willing to spend more money to their loyal brand (Dowling and Uncles, 1997 as cited in Schoenbachler, Gordon and Aurand., 2004). The positive word of mouth that brought by brand loyalty is the mechanism which enable corporation to save the marketing cost (Rundle-Thiele & Mackay, 2001).…”
Section: Brand Loyaltymentioning
confidence: 99%